Dark and Light Triad in Relation with Social Anxiety - Mehta, Yuv (Thapar university, 2022)
Abstract The present study focuses on understanding how the dark and light triad relates to social anxiety. It was investigated using three scales,Dark Triad of Personality (D3-Short), the Light Triad Scale,the Liebowitz's Social Anxiety Scale (LSAS). The total sample consisted of 78 subjects (45 females and 33 males). The age range of the participants is 18-40 years. The research objective was to study the Dark and Light Triad with Social Anxiety. The findings of this study indicate that the Dark triad is negatively correlated with social anxiety. Further, the light triad is positively correlated with social anxiety.The present study is a humble effort to analyze the relationship between the above-mentioned variables with the help of correlation and regression.
Keywords: Dark triad, narcissism, machiavellianism, psychopathy, light triad, empathy, compassion, altruism, social anxiety.